Prototyping and usability testing of a metadata schema creation and selection module for OpenBiblio - Kangleon, Ebony R.; Torralba, Christienne Mikhaille C.; Baylas, Bianca Rei T. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
The development via customization of existing integrated library systems (ILS) is not an unfamiliar thesis topic, especially in the UP School of Library and Information Studies (UP SLIS). Numerous studies have been conducted on the various stages of the development: analysis, design, prototype, usability, implementation, and evaluation. However, most of these are concerned with a specific institution; very few intended their studies to be adaptable to other institutions which may or may not share the same library policies. With this in mind, the study focused on developing a prototype and conducting a usability test for a metadata schema selection and creation module for OpenBiblio that is targeted towards special libraries and institutions. This research partially adapted a previously proposed design as its basis for the module from the undergraduate thesis, Design of an Integrated Library System with Metadata Schema Creation and Selection through Entity Relationship Modeling of Selected Special Libraries in Metro Manila by Santillan (2010), with minor modifications as seen by the researchers. Agile methodology was used in planning, structuring and prototyping the system. Three metadata modules were added to OpenBiblio, namely, Metadata Object Description Schema (MODS), a combination of Simple Dublin Core (SDC of simply DC) and an application profile of Dublin core called Dublin Core Education (DC-ED), and lastly, a combination of the Categories of the Description Works of Art (CDWA) and Cataloging Cultural Objects (CCO).
Ten representative users from ten special libraries and institutions participated in the usability test which consisted of a series of task scenarios and a post-test evaluation using the System Usability Scale by Tullis and Stetson (2004). The results show a very high success rate for task completion while the results for task performance show that majority of the representative users found most of the tasks easy; however, almost everyone had a hard time when it came to the tasks involving the Add Record modules especially OpenBiblio's own New Bibliography module. All participants were in agreement in how they perceive the software to be in terms of case of use and perceived satisfaction rate but the customized software achieved a SUS score of 62.3%, which according to Hamilton (n.d.), is below the average score of 66%. The results of the usability test only show that more work needs to be done in improving the system and its features.
It was concluded that task time and degree of difficulty vary for each person in completing and performing the tasks. These attributes depend on the tasks given and the proficiency and familiarity of the person with the system. Nevertheless, the overall response for the customized system is positive. Furthermore, the considerably high percentage of success rates for the Task Completion part and the fact that no one failed the task-based test based on the results of the Task Performance part only show that the customized system is effective.
Recommendations included deployment and implementation of the system with additional features and further improvements and modifications on the metadata modules. A usability test is also needed to evaluate the system when deployed in order to test its effectiveness.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Online library catalogs; Metadatabases; Open source software